Pengaruh Celebrity Endorser Terhadap Brand Equity melalui Self Brand Connection bagi Pengguna Honda Vario - Mahmud (Lembaga Pengembangan Kinerja Dosen, 2021)
This study was conducted with the aim to examine the effect of celebrity endorser on brand equity with self brand connection as a variable that intervened Honda Vario users in Semarang. The population in this study is the Honda Vario user. The number of samples in this study were 150 samples. The sampling technique used was purposive sampling, with the provisions that at least respondents collected 17 years, consumers had used a Honda Vario and lived in Semarang City. Data analysis method used is structural equation modeling. The direct test results between celebrity endorser and brand equity show that there is a significant and positive influence. The direct test results between celebrity endorser on self brand connection showed positive and significant significance. The direct test results between self brand connection and brand equity show that there is a significant and positive influence.